Charismatic Christians genuinely religious, genuinely modern - Kessler, Christi (2006)
The article discusses the findings of an empirical study on religious change in the Philippines conducted in 2003. The findings challenge the common assumptions about the middle class character of the Catholic Charismatic Renewal movement and the predominantly poor and uneducated followers of non-Catholic charismatic mass organizations. Three types of religiosity are identified: sociocultural, orthodox, and charismatic, The findings indicate that the phenomenon of charismatic Christianity in the Philippines cannot be reduced to socioeconomic or political factors; rather, charismatic religiosity is a genuinely religious phenomenon that cuts across social classes. This religious phenomenon is interpreted as a way of coping with the challenges of modernization processes.
Includes bibliographic references (p. 583-584).
Keywords: Catholic charismatic movement; Pentecostalism